Lagrangian Residence Time in the Bay of Gdańsk, Baltic Sea - Dippner, Joachim W.; Bartl, Ines; Chrysagi, Evridiki; Holtermann, Peter; Kremp, Anke; Thoms, Franziska; Voss, Maren (Frontiers in Marine Science, 2019)
The impact of synoptic scale and mesoscale variability on the Lagrangian residence time (LRT) of the surface water in the Bay of Gdansk was investigated using the results from an eddy-resolving model. The computed LRT of 53–60 days was up to four times longer than the estimated flushing time reported by Witek et al. (2003). The highest residence times were those of Puck Bay and near the coast, below 50 m water depth, especially during the winter. These sites also had the highest annual mean in LRT. During the summer, when the level of biological activity is high, the LRT distribution was very heterogeneous and patchy, possibly due to the eddy field and to variable wind forcing. Long-term run tracking of the inflowing water from the Vistula River showed a broad spectrum of tracer distribution. The potential impact of a much higher LRT on the near-coastal nitrogen cycle, coastal filter function and genetic differentiation is discussed, and the consequences for coastal zone management are considered. The incorporation of residence time into the Marine Strategy Framework Directive descriptors would result in an improved, unbiased evaluation of good environmental status.